CEO Characteristics and Earnings Management: A Study of Manager Tenure, Age, Gender, and Overconfidence - Chen Sitao; Tzavara Dionisia; Argyropoulou Maria; Koufopoulos Dimitrios; Argyropoulou Rachel (Studies in Business and Economics)
Corporate scandals over the past few decades underline the importance of robust corporate governance mechanisms to monitor and control managerial behaviour. Earnings management, where accounting techniques are used to present a company’s financial position more favourably than it actually is, can affect financial reporting quality and the company’s financial reputation. Our study explores how CEO characteristics, such as tenure, gender, age and overconfidence, influence corporate earnings management. Using earnings and executive characteristics data for A-class companies listed in Shanghai and Shenzhen stock exchanges between 2016 and 2020, the research employs multiple regression analysis to empirically analyse the impact of manager characteristics on corporate earnings management. We find that CEOs with longer tenure, male and high self-confidence are more likely to participate in corporate earnings management. Additionally, firm size and asset-liability ratio are positively related to corporate earnings management behavior. While previous studies mainly use data from US companies, this research contributes to the literature by using data from non-US companies, addressing the call for more empirical studies to understand how top executives’ demographic characteristics impact earnings management in different contexts.